Models and interactions of intensive training and sport performance of 14-15-year old athletes in rhythmic gymnastics - Rutkauskaite, R.; Skarbalius, A. (Education. Physical training. Sport, 2012)
Research background and hypothesis. The efficacy of athlete`s sport performance depends on the targeted training in certain periods, organization, management, individual adaptation of an athlete to the loads of training and competitions. Research aim of this work was to determine the impact of intensive training on sport performance of 14-15 year old athletes in rhythmic gymnastics and their optimization. Research methods. The experiment resulted in modeling two different training programs and establishing the structure of the content of the training programs, as well as athletes` sports performance. The training loads protocols registered the time for choreography, element mastering, competitive routines and athletic training in each training session. The efficacy of the training programs was established registering the realization of competitive activities under competitive conditions according to the number of points received by the gymnast of each training program and according to the place won. When we tried to establish if the training sessions and competitive loads matched the specificity of competitive activities, we registered the changes in the athletes` heart rate during different training sessions. Research results. Training of athletes in two training programs was different - their training loads were not significantly different - from 672 to 697 hours a year, as well as the indices of the training days - from 5.4 to 5.6 days a week, but the training content differed significantly. In most effective training program choreographic training dominated (30.9%). Statistically significant differences (p < 0.05) were found in the indices of explosive strength and muscular power, specific endurance and coordination movement abilities. At the beginning of the season and at the end of it the realization of the body movement technique performing routines with different tools was not different (p > 0.05). Discussion and conclusion. Sports performance of 14-15-year-old athletes in rhythmic gymnastics was mostly influenced by the time for mastering competitive routines (r = 0.836); however, the research did not establish differences in intensifying training. Besides the importance of integral athletic fitness, explosive strength, and strength endurance, the research established the significance of aerobic fitness (r = 0.704) for sports performance. Moreover, the significance of body composition indices increased in comparison with previous training years: body height (r = -0.819), body weight (r = -0.657), and BMI (r = -0.836).